Acute induction of anxiety in humans by delta-9-tetrahydrocannabinol related to amygdalar cannabinoid-1 (CB1) receptors. Issue 1 (December 2017) - Bhattacharyya, Sagnik; Egerton, Alice; Kim, Euitae; Rosso, Lula; Riano Barros, Daniela; Hammers, Alexander; Brammer, Michael; Turkheimer, Federico; Howes, Oliver; McGuire, Philip
Abstract Use of Cannabis, the most widely used illicit drug worldwide, is associated with acute anxiety, and anxiety disorders following regular use. The precise neural and receptor basis of these effects have not been tested in man. Employing a combination of functional MRI (fMRI) and positron emission tomography (PET), we investigated whether the effects of delta-9-tetrahydrocannabinol (delta-9-THC), the main psychoactive ingredient of cannabis, on anxiety and on amygdala response while processing fearful stimuli were related to local availability of its main central molecular target, cannabinoid-1 (CB1) receptors in man. Fourteen healthy males were studied with fMRI twice, one month apart, following an oral dose of either delta-9-THC (10 mg) or placebo, while they performed a fear-processing task. Baseline availability of the CB1 receptor was studied using PET with [11 C]MePPEP, a CB1 inverse agonist radioligand. Relative to the placebo condition, delta-9-THC induced anxiety and modulated right amygdala activation while processing fear. Both these effects were positively correlated with CB1 receptor availability in the right amygdala. These results suggest that the acute effects of cannabis on anxiety in males are mediated by the modulation of amygdalar function by delta-9-THC and the extent of these effects are related to local availability of CB1 receptors.